The Plasma Focus—Numerical Experiments, Insights and Applications - Lee, S.*; Saw, S. H. (Springer Nature Singapore Pte Ltd., 2017)
In this chapter we review numerical experiments using the Lee Model code. We describe the contributions made by this code in the past 30 years in the light of overall work on simulations already documented in the area of plasma focus. The plasma focus exhibits interesting phenomena ranging from electromagnetically driven dynamics to copious radiation including ions, electrons, X-rays, characteristic soft X-rays, fusion neutrons, to fast ion beams (FIB) and fast plasma streams (FPS), to anomalous resistivity resulting from a range of plasma instabilities, to plasma states of extreme high-energy density (HED) achieved through radiative cooling and collapse. The Lee Model code is successful in modelling many of these multi-faceted aspects of the plasma focus. The physics, equations and contributions of the code are explained in this chapter. Its success on so many fronts is attributed to its use of 4 parameters (fitted to a measured current waveform) which in one sweep incorporates all the mechanisms and effects occurring in the plasma focus including mechanisms and effects difficult to compute or even as yet unrecognized. The simple premise is that the sum total effect of all these mechanisms and phenomena is represented in net result by mass field and force field distributions which in the gross sense are represented by a mass swept-up factor fm and an effective current factor fc in the axial phase and two corresponding factors in the radial phase, up to the end of the focus pinch. Once matched, the fitted model parameters assure that the computation proceeds with all physical mechanisms accounted for, at least in the gross energy and mass balance sense.